Penegakan Hukum Animal Abuse dan Peningkatan Kesejahteraan Hewan di Kota Makassar Melalui Veteriner Forensik - Febrianti, Ira; Ramadhansyah Prasetia, Muhammad; Nurfadilla, Nurfadilla; Aulia Ramadhan, Salsabila; Rayhan Putra Hasrun, Ahmad; Djaelani Prasetya, Muhammad (UNES Law Review, 2023)
Animal welfare is proven by fulfilling the 5 principles of animal freedom or five freedoms, namely freedom from hunger and thirst, from discomfort, from pain, injury, or disease, freedom to express normal behavior, and freedom from fear and distress. This research focuses on dogs and cats because in line with cases that occurred in Makassar City, these two animals are often victims of violence. The research aims to describe the public's perception in Makassar City regarding animal welfare, the police's perception of forensic veterinary, the application of forensic veterinary as a law enforcement tool, as well as solutions for implementing forensic veterinary to protect animal rights in Makassar City. This research uses a mixed method with a Sequential Explanatory approach model. The first research used quantitative methods to answer the first to third problem formulations and qualitative methods to answer the fourth problem formulation. Data analysis using quantitative methods through descriptive analysis using the SPSS application. Meanwhile, qualitative data analysis involves reducing the data to concluding. The research results show that public knowledge regarding animal welfare is very low and police investigators' knowledge of veterinary forensics is quite good, but not yet in line with its implementation. Therefore, veterinary forensics is present as an effort to enforce the law against acts of animal violence in realizing animal welfare in the city of Makassar.